(untitled) (Discourse of Law and Administration, 2025)
Within the framework of this article, the author intends to present the issues related to the use of autonomous vehicles and the actions needed to safely introduce them into widespread use. By analysing current national and international legislation, the author will set out the legal framework for the operation of fourth generation autonomous vehicles. Author will then collate current legislation with technical and information technology information throughout the publication to provide a cross-cutting and comprehensive presentation of autonomous vehicles. The author will reflect on the future of the technical infrastructure by referring to existing solutions from non-legislative fields. On the basis of the conclusions reached and analysis of the issue in question, based on the facts from the technical fields, the author will attempt to formulate de lege lata and de lege ferenda conclusions, enabling the proper introduction of autonomous vehicles on the roads. The use of autonomous vehicles in public transport and the correct operation of these vehicles in public transport will also be addressed. In this publication, the author will attempt to provide a summary overview of the various factual and legal actions which, in the author’s opinion, should be considered by the legislator as part of the legislative process.